Makáriosz alkotmányreformja és a ciprusi válság - Kalmár, Zoltán (Acta Scientiarum Socialium, 2012)
The constitutional reform of Makarios and the crisis in Cyprus. In the mid-1950s intercommunal violence erupted on Cyprus. This led to the London-Zurich Agreements, signed by Britain, Turkey, and Greece on 11 and 19 February 1959. As a result, on 16 August 1960 the independent Republic of Cyprus was born, governed under a presidential system. Presidential elections were held on the island on 13 December 1959. Archbishop Makarios was elected president of the new republic. Greek Cypriot-Turkish Cypriot unification processes nevertheless failed to start in the sovereign parliamentary republic, despite the very fact that the state was in the showcase of international political attention. In November 1963, President Makarios proposed 13 amendments to the Constitution, but Turkey and the Turkish Cypriots rejected these presidential proposals, and violence broke out between the Greek Cypriot and the Turkish Cypriot communities. The purpose of the present study is to illustrate in detail the principles underlying the Constitution of Cyprus, which is based on international conventions, and critically examine the attempt of President Makarios to revise and update the Constitution of the Republic of Cyprus.
Keywords: crisis; reform; constitution